2015
DOI: 10.1089/jmf.2014.3411
|View full text |Cite
|
Sign up to set email alerts
|

A Standardized Extract of Rhus verniciflua Stokes Protects Wistar Rats Against Lipopolysaccharide-Induced Acute Inflammation

Abstract: Rhus verniciflua stokes (RVS) (Anacardiaceae) has been traditionally used as a folk remedy for gastritis, several cancers, and various metabolic diseases. The present study evaluated the anti-inflammatory effect of RVS extract standardized to fustin content using lipopolysaccharide (LPS)-stimulated rats. The rats were randomly divided into six groups and intragastrically administered 0, 100, 250, or 500 mg/kg body weight (bw) of RVS or 15 mg/kg bw of fustin for 14 days. LPS was intraperitoneally injected 18 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Several animal studies have reported that R. verniciflua exerted beneficial effects on inflammation and several metabolic diseases [ 16 , 17 ] and protective effects against drug toxicity [ 18 ]. The previous studies suggested that R. verniciflua would be a potent candidate for drug development to treat chemotherapy-induced side effects, particularly emesis.…”
Section: Introductionmentioning
confidence: 99%
“…Several animal studies have reported that R. verniciflua exerted beneficial effects on inflammation and several metabolic diseases [ 16 , 17 ] and protective effects against drug toxicity [ 18 ]. The previous studies suggested that R. verniciflua would be a potent candidate for drug development to treat chemotherapy-induced side effects, particularly emesis.…”
Section: Introductionmentioning
confidence: 99%
“…A similar study in which rats were orally given RVS extract at 100 mg/kg and 500 mg/kg for 2 weeks and then challenged with intraperitoneal LPS showed a significant reduction in IL-6 protein and a marginal reduction in TNF- protein in the liver [36]. These hepatic cytokine concentrations were measured 16 h after LPS stimulation [36]. However, the peak response of serum TNF- is approximately 1 h after intraperitoneal challenge with LPS and rapidly declines [31].…”
Section: Rvs Extract Suppressed the Systemic Response To Lpsmentioning
confidence: 80%
“…This is likely due to the fact that macrophages are continuously exposed to LPS in vitro, but LPS is rapidly cleared by the liver in vivo [35]. A similar study in which rats were orally given RVS extract at 100 mg/kg and 500 mg/kg for 2 weeks and then challenged with intraperitoneal LPS showed a significant reduction in IL-6 protein and a marginal reduction in TNF- protein in the liver [36]. These hepatic cytokine concentrations were measured 16 h after LPS stimulation [36].…”
Section: Rvs Extract Suppressed the Systemic Response To Lpsmentioning
confidence: 99%
“…This is likely due to the fact that macrophages are continuously exposed to LPS in vitro, but LPS is rapidly cleared by the liver in vivo [35]. A similar study in which rats were orally given RVS extract at 100 mg/kg and 500 mg/kg for 2 weeks and then challenged with intraperitoneal LPS showed a significant reduction in IL-6 protein and a marginal reduction in TNF-α protein in the liver [36]. These hepatic cytokine concentrations were measured 16 h after LPS stimulation [36].…”
Section: Discussionmentioning
confidence: 99%